2009
DOI: 10.3201/eid1502.081166
|View full text |Cite
|
Sign up to set email alerts
|

Face Mask Use and Control of Respiratory Virus Transmission in Households

Abstract: Mask use is associated with low adherence, but adherent mask users are significantly protected against seasonal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
374
3
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(404 citation statements)
references
References 24 publications
14
374
3
13
Order By: Relevance
“…Although the main focus of these studies was the effectiveness of interventions, adherence and in some cases tolerability of measures were also investigated. Of these three studies two reported on adherence to wearing facemasks [2,3], which was lower compared to our study. Furthermore, we noted substantially increasing adherence after participants had received detailed instructions during a first household visit (Figs 1 and 2).…”
contrasting
confidence: 94%
See 2 more Smart Citations
“…Although the main focus of these studies was the effectiveness of interventions, adherence and in some cases tolerability of measures were also investigated. Of these three studies two reported on adherence to wearing facemasks [2,3], which was lower compared to our study. Furthermore, we noted substantially increasing adherence after participants had received detailed instructions during a first household visit (Figs 1 and 2).…”
contrasting
confidence: 94%
“…In recent years, evidence has emerged suggesting that non-pharmaceutical interventions (NPI) such as surgical facemasks or intensified hand hygiene may be effective in preventing influenza transmission when used in households or university residence halls [1][2][3]. In addition to the effectiveness of these interventions, however, it seems equally important to understand which factors influence adherence and tolerability of NPI [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A facemask, as a kind of simple and convenient respirator, is widely used in daily life. It has been demonstrated that wearing facemasks for a long time can reduce the probability of infection from influenza-like illnesses (MacIntyre et al, 2009;Natarajan et al, 2016;Lin et al, 2017). Especially, functional facemasks are recommended for frontline healthcare workers to prevent splashes and sprays of blood, body fluids and the spread of infection from the wearer (Siegel et al, 2007;Agarwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it became obvious, to our intense embarrassment, that it is not at all clear how the influenza virus transmits from person to person. 17,18 With such a dearth of knowledge, how can we utilise to the fullest extent the third and fourth defence zones, the home front and hygiene? A scientific consensus shows that patients with A/swine (H1N1) influenza excrete virus in the upper airways and, upon coughing and sneezing, distribute a droplet cloud of influenza virions which are trapped in these droplets to be inhaled by persons close by, say within one metre.…”
Section: A Modern Application Of the Principles Of Hygienementioning
confidence: 99%